Multicentered audit of compliance to WHO surgical safety checklist and wrong-site surgery & anesthesia in Thailand: The Perioperative and anesthetic adverse events study in Thailand (PAAD Thai) study - C. Somchat (2020)
© 2019 Medical Association of Thailand. All rights reserved. Background: The Royal College of Anesthesiologists of Thailand (RCAT) hosted the Perioperative and Anesthetic Adverse events in Thailand (PAAd Thai) study perioperative adverse events in 2015. Objective: To investigate the compliance to World Health Organization (WHO) surgical safety checklist among patients with incident reports and the incidence of wrong patient, wrong site or wrong side of surgery or anesthesia. Materials and Methods: After approval of the Institutional Ethical Committee, informed consent was waived due to the observational study design. Anesthesia providers and site managers of 22 hospitals, including eight medical schools and 14 service-based hospitals, across Thailand were requested to fill-in a structured incident reporting form of the RCAT (both closed-ended and opened-ended) regarding several occurrences such as cardiac arrest, difficult intubation, esophageal intubation, and wrong-site surgery. Three senior anesthesiologists reviewed the incident reports. Any discrepancy was resolved by discussion to reach consensus. Results: Among 2,206 incident reports of any adverse events during the 12-month period in 2015, there were high compliance of patient identification (80%), use of pulse oximeter (92%), anesthesia checklist completion (92%), and drug allergy inquiry (79%). Low compliance items were site marking (44%), prophylactic antibiotics before incision (52%), post-operative care planning (47%), and communication of possible post-operative problems (48%), according to WHO surgical safety checklist. Among the 333,219 anesthesia undergoing surgeries, there were six cases (two wrong persons, two wrong side, and two wrong side anesthetic procedure) with an incidence of 0.18 (95% CI 0.04 to 0.32) per 10,000. The six cases (100%) were human error and included five incidents (83%) that were system related such as inadequate personnel, lack of guidance for ultrasound guided nerve block etc., five incidents (83%) that could not prevented by the WHO surgical safety checklist, and two (33%) that were near-miss events. Conclusion: Despite moderate to high compliance of WHO SSC in Thai hospitals, wrong-site-surgery or anesthetic procedure still occurred. Most of the incidents were due to human error. A systemic approach to improve communication, identify adequate personnel, and adhere to the pre-procedural specific checklist, such as guidance for ultrasound guided nerve block, are suggested.